NURSING DIAGNOSIS IN PATIENTS WITH HYPOGLYCEMIA IN THEEMERGENCY DEPARTMENT - Hidayati, Nur; Aldia, Melani Adinda Putri; Maghfuroh, Lilis (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Hypoglycemia is a condition involving decreased blood glucose levels. It can cause symptoms affecting multiple systems and have serious consequences if left untreated. Nurses play a crucial role in swiftly and appropriately detecting and treating hypoglycemia in the emergency department. Research on nursing diagnoses was the first step in determining interventions for hypoglycemic patients in the emergency department of the Muhammadiyah Babat General Hospital. The study employed a descriptive retrospective design using secondary data from medical records. The study sample included 73 hypoglycemia patients admitted to the emergency room from January to December 2024, selected using consecutive sampling, and data was collected on May, 2025. The data was analyzed descriptively. The results showed that all patients experienced similar signs and symptoms: low blood glucose levels, drowsiness, decreased appetite, weakness, dizziness, strange behavior, and physical weakness. The nursing diagnosis that emerged for all patients was blood glucose level instability. These findings suggest that hypoglycemia has a consistent clinical impact and requires a structured nursing response. Decreased intracranial adaptive capacity, a diagnosis listed in the nursing pathway that is usually associated with severe hypoglycemia, was not found in this study. This may be due to limitations in neurological assessments and supporting examinations.